Narrativas de adolescentes en conflicto con la Ley penal, de la ciudad de Riohacha: una aproximación a la comprensión de un fenómeno familiar - Salcedo Valencia, Edgard Manuel (Universidad Antonio Nariño, 2023)
This research analyzed the family communication and identified the emotional ties of four teenagers in conflict with the law, looking for an approach to the understanding of the dynamics of families. Their approach is qualitative and through induction is intended to achieve a construction based on logic and the feelings of young people.